Komunikasi Antarbudaya Dalam Proses Asimilasi Pernikahan Jawa dan Minangkabau (Studi Deskriptif Kualitatif Komunikasi Antarbudaya dalam Proses Pernikahan Jawa dan Minangkabau) - Hestiana, Arika, Agus Triyono, M.Si, Nieldya Nofandrilla, MA (2014)
Intercultural communication is communication that involves interaction among people with different perceptions about culture. Intercultural communication is needed by every people to communicate with another people in different culture. Two cultures difused in a marriage requires a deeper understanding to make an effective communication. The subjects in this study are three marriage couples, each couple is Javanesse married with Minangkabau. The aim of this research to determine the intercultural communication in the process of assimilation of Javanese and Minangkabau marriage. This study uses descriptive qualitative research methods. Descriptive research is used to further explore the information from the subject under study. Finally, the result of this research, such as dissolving communication process by minority culture (Java) refers with the majority culture (Minangkabau). Second, there is a tolerance about differentiation culture in their marriage. The last, the couple put their religion as a path for trough their life.